Three-dimensional shape measurement for thin objects based on hue-height mapping using color-encoded fringe projection. (October 2018) - Wan, Yingying; Cao, Yiping; Chen, Cheng; Fu, Guangkai; Wang, Yapin
Three-dimensional (3D) shape measurement based on hue-height mapping using color-encoded fringe projection is proposed for thin objects. The projected color-encoded fringe pattern is encoded by three sinusoidal fringe patterns with 2π/3 shift phase in between into red (R), green (G) and blue (B) channels, separately. It is found that the hue component is of periodicity with the same period as the sinusoidal fringe pattern in the R channel of the color-encoded fringe and the hue distribution in a period is of monotonicity. While this color-encoded fringe pattern is projected onto an object, as long as the deformation of the captured deformed color fringe pattern is not out of a period, the 3D shape of the measured object can be reconstructed directly by hue-height mapping. This method is concise and fast with no color calibration to remove color crosstalk and no time-consuming phase extraction or phase unwrapping. The experimental results show the feasibility and the practicability of the proposed method.